Structural Microdomains in the Lateral Plasma Membrane of Cochlear Outer Hair Cells - Zhang, Ming (Springer-Verlag, 2002)
The basal and lateral regions of the plasma membrane of cochlear outer hair cells are structurally and functionally distinct. The lateral region contains thousands of motor proteins but few voltage-gated channels. The basal region, conversely, contains a high number of voltage-gated channels but is devoid of motor proteins. It has been suggested that the cortical cytoskeleton is responsible for maintaining this regional distinction. Toward elucidating the structure of the outer hair cell's electromotile mechanism, we investigated the physical organization of the lateral plasma membrane in living guinea pig outer hair cells by analyzing the distribution pattern of the anionic long-chain carbocyanine SP-DiIC18(3) within this area, before and after electrical stimulation and with an intact and a disrupted cytoskeleton. We observed punctate, intensely fluorescent patches as well as areas of weaker fluorescence, with clear local maxima and minima, upon labeling the cells with this membrane-soluble probe. This discrete distribution of SP-DilC18(3) suggests that the lateral plasma membrane of guinea pig outer hair cells may be composed of small structural domains (microdomains). Disrupting the cytoskeleton with either trypsin or toxin B from Clostridium difficile did not change this pattern of distribution, thus indicating that this treatment did not facilitate the lateral diffusion of the probes. Electrical stimulation using whole-cell patch-clamp techniques, on the other hand, induced two responses: fast motility and reversible displacement of the fluorescent probes. Both responses were inhibited by internal perfusion with salicylate, while disruption of the cytoskeleton did not inhibit OHC fast motility but affected the electrically induced redistribution of fluorescent probes. Together, these results suggest that the lateral plasma membrane of guinea pig outer hair cells contains structural microdomains and that the cytoskeleton does not appear to be playing a major role in maintaining the lateral separation of these distinct molecular regions.